Le Salon. Anthology 2011-2016. - Bayar, Devrim; Verhack, Valerie (Brussel : Triangle Books, 2019)
Oorebeek, Willem ; Cottin, Audrey ; Anesiadou, Danai ; Geys, Jef ; Nys, Sophie ; Dedobbeleer, Koenraad ; Meert, Julie ; wachtler, Peter ; Kuri, Gabriel ; Agency ; Geyskens, Vincent ; Bernadet, Jean Baptiste ; Curlet, François ; Foulon, Olivier ; Lommée, Catherine ; Moulène, Jean-Luc ; François, Samuel ; Thys, Eric ; Wambaq, Freek ; Swennen, Walter ; Auder, Michel ; McKenzie, Lucy ; Nadashi, Shelly ; Koks, Aukje ; Fabris, Eva
Catalogus naar aanleiding van de werking van Le Salon van 2011 tot 2016
boek